Breathwork : use the power of breath to energize your body and focus your mind - Westmacott-Brown, Nathalia, 1971- (Little book of self care (DK Publishing, Inc.), 2019)
New science has revealed the effectiveness of breathwork to balance the body, focus the mind, relieve stress, control anxiety, boost self-esteem, address anger issues, and more. Here we give you over 50 step-by-step techniques that you can use at home, with accurate expert advice on body position, depth of breath, speed of breath, visualization, duration and repetition. Techniques include conscious connected breathing, pranayama, holographic breathwork, and qi gong breathwork - and you are shown how to do these accurately and safely. Slow down, be aware of your breath, recognize your own unique rhythms, and then learn how to breathe mindfully and with control and use different breath practices for targeted outcomes - from overcoming insomnia to releasing anger to relieving depression.